PEMODELAN DAN PERANCANGAN SUPPLY CHAIN MANAGEMENT PADA PRODUK SPAREPART MOBIL - Anna Dara Andriana; Mohammad Syukron Alawy (LPPM Unbaja, 2023)
Supply chain management is a supply chain that regulates the production process of raw goods into semi-finished or finished products. the processes in it, namely the procurement of raw materials, warehouse monitoring, production monitoring to delivery monitoring must be carried out properly so that the company's business processes are not disrupted. problems that may arise, namely the difficulty of selecting suppliers, the difficulty of determining the amount of procurement of raw materials, the difficulty of monitoring production and the difficulties in the distribution process can be resolved by building an SCM information system. The purpose of this system is to simplify the process of each chain in supply chain management. the result of this application can assist companies in monitoring the supply chain processes that occur in the company.